Effect of a Lactobacillus sakei and Staphylococcus xylosus protective culture on Listeria monocytogenes growth and quality traits of Italian fresh sausage (salsiccia) stored at abusive temperature. Issue 1 (14th December 2020) - Pedonese, Francesca; Torracca, Beatrice; Mancini, Simone; Pisano, Sonia; Turchi, Barbara; Cerri, Domenico; Nuvoloni, Roberta
Abstract: Fresh sausages are not always thoroughly cooked before consumption and can support the growth of pathogenic microorganisms, especially when stored at incorrect temperatures. The aim of this study was to verify the growth of Listeria monocytogenes in Italian salsiccia stored at 2 °C, 7 °C and 12 °C for 9 days (t9) with (PC+) and without (PC–) a commercial protective culture ( Lactobacillus sakei and Staphylococcus xylosus ). L. monocytogenes PC + counts were statistically different from PC–, after 7 days (t7) at 7 °C and at 12 °C. At 2 °C, they increased in PC + by 0.03 and 0.36 log CFU/g vs. 0.25 and 0.91 in PC–, at t7 and t9. Moreover, quality characteristics (total aerobic counts, colour parameters, TBARS values, pH, sensory attributes) were assessed in fresh sausages stored at 7 °C. Significant differences were obtained in PC + samples at t7 for Pseudomonadaceae and Enterobacteriaceae (about 2 log CFU/g). Yeasts and moulds and Brochothrix thermosphacta were also significantly lower in PC + samples. PC + samples were more acidic than PC–, with statistically different colour parameters values particularly at the external surface; raw sausages resulted sensorially discernible at t7, whereas PC + and PC– cooked samples did not show any significant sensory difference. The studied protective culture proved to be a useful tool to increase safety and microbiological quality of salsiccia at abusive storage temperature, effectively limiting the growth of L. monocytogenes and Gram negative spoilage microorganisms, with some sensory drawbacks, especially at the end of the shelf life. HIGHLIGHTS: The tested culture improves the microbial safety of salsiccia. It reduces the growth of spoilage microorganisms, especially Pseudomonadaceae and Enterobacteriaceae. It mainly influences colour and acidity evolution of the raw product with no sensory drawbacks in the cooked product.